Peran Sektor Unggulan dalam Mewujudkan Pembangunan Ekonomi Inklusif di Kabupaten Timor Tengah Utara - Frederic Winston Nalle; Dominikus Kopong Duli; Maria G. Maya Nai Mau (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
Inclusive economic development is a development that prioritizes the aspect of equity to realize economic justice for all levels of society. Therefore, each local government is expected to be able to optimize the leading sector so that it can act as the locomotive of the regional economy. This study aims to identify and analyze changes and shifts in economic sectors, classify and map leading sectors and formulate appropriate strategies for inclusive economic development. The analytical tools used are Shift Share analysis, Klassen typology, and SWOT analysis. The type of data used is primary data for the needs of SWOT analysis and secondary data for Shift share analysis and class typology. The data used are GRDP and Employment data per sector from 2015-to 2020. The results show that through Shift Share analysis, in general, the industry with the most significant National Share (Ns), Proportional Shift (Ps) value, and Differential Shift (D) value is the agricultural sector. Klassen's Typology analysis shows that the sectors developing and overgrowing are the farm and manufacturing industries. Therefore, the strategy that is considered appropriate to realize inclusive economic development through the concept of creating a leading sector is to apply the Strength-Opportunity (SO) Strategy, where the government is expected to be able to take advantage of all forms of existing strengths while taking into account the various opportunities they have.